The Relationship Between Pregnant Women’s Knowledge and Compliance at the Tinongko Community Health Center - Meyva Silvia Lasuasa; Tut Rayani Aksohini Wijayanti (Jurnal Medika Nusantara, 2025)
Background: Compliance with antenatal care (ANC) visits is an important factor in preventing pregnancy complications and reducing maternal mortality. However, there are still pregnant women who do not complete ANC visits according to standards. The knowledge of pregnant women is thought to play a role in shaping compliance with ANC services. Objective: This study aims to analyze the relationship between the level of knowledge of pregnant women and compliance with antenatal care visits at the Tinongko Community Health Center. Methods: This study used an analytical observational design with a cross-sectional approach. The study population consisted of all pregnant women who received ANC services at the Tinongko Community Health Center, with a sample of 60 respondents. Data were collected using a structured questionnaire and verification of the KIA book. Data analysis was performed using univariate and bivariate analysis with the chi-square test. Results: The results showed that there was a significant relationship between the level of knowledge of pregnant women and their compliance with ANC visits (p < 0.05). Pregnant women with good knowledge tended to be more compliant than those with adequate or poor knowledge. Conclusion: The knowledge of pregnant women is significantly related to their compliance with antenatal care visits. Improving health education for pregnant women at the primary care level has the potential to increase ANC compliance and support improvements in maternal and fetal health outcomes.